Real-time task scheduling with fuzzy uncertainty in processing times and deadlines - Muhuri P.K.; Shukla K.K. (My University, 2025)
In real-time systems, scheduling algorithms play the vital role of devising a feasible schedule of the tasks. The scheduling algorithm designer faces uncertainty associated with the timing constrains of the real-time tasks. This paper considers fuzzy timing constraints by modeling the real-time tasks with fuzzy deadlines and fuzzy processing times with different membership functions. Comparative studies and some interesting findings based on simulation experiments are reported. © 2006 Elsevier B.V. All rights reserved.